Evaluating climate change towards sustainable development - Kumaran, Vikniswari Vija; Haron, Nazatul Faizah; Ridzuan, Abdul Rahim; Saudi, Nur Surayya; Sapuan, Noraina Mazuin (Academic Press, Elsevier, 2022)
There is a growing awareness that our planet Earth is rapidly changing, and scientists have related those occasions to climate change. The Earth’s surface temperature has been gradually rising since the late 19th century. The change is the result of a huge scale release of carbon dioxide (CO2)-related products into the air. Since 2001, CO2 emissions have been more rapid and seen in an upward trend. Banett (2017) indicated that about 97% of peer-reviewed climate studies conclude that the sources of higher CO2 release that causes climate change are derived from burning fossil fuels, industrial activities, and deforestation. The overall outcomes of an increasing trend have resulted in rising sea temperatures, coral reef corruption, and harming the ocean life. The loss of man mass, floods, and other outcomes of rising sea levels includes human passings and property losses worth loads of billions of dollars. Global warming has other disastrous outcomes, such as mortality from heat waves, starvation, storms, and fires, to name a couple. The overall misfortune from these occurrences amounts to trillions of dollars per year, increasing year after year.